Electrochemical study of nickel nanoparticle graphene composite - Nur Aisyah , Mohamad Rosli (2012)
This project entitled the electrochemical study of Nickel nanoparticle graphene composite. Graphene is a two-dimensional crystal consisting of a monolayer of carbon atoms arranged in a honeycomb lattice which is extracted from graphite. It is capable to produce a high oonductivity of electricity and has a high surface area. Nanoparticles are generally considered an invention of modern science. The interesting and sometimes unexpected properties of nanoparticles are therefore largely due to the large surface area of the material, which dominates the contributions made by the small bulk of the material. Aside from graphene and nanoparticle interesting solid state chemistry and structural attributes, these two compounds exhibit interesting magnetic, optical, and electrochemical properties and thus have great potential for device applications (e.g. molecular magnets, electrodes and rechargeable batteries). Thus, these materials have raised renewed and growing interest in the electrochemical field. In this project, graphene was synthesized from graphite by electrolytic exfoliation using poly(sodium-4styrenesulfonate) as an effective electrolyte while Nanosized nickel was prepared by a simple co-precipitation method. The surface area of graphene was measured using BET method and functional group was characterized by FTIR. X-ray diffraction was performed on the as-prepared nickel nanoparticle and confirmed its crystal structure. These two materials were grinded together to produce nickel nanoparticle graphene composite. The electrochemical behavior of the sample was studied by cyclic voltammetry (CV), and electrochemical impedance spectroscopy (EIS).